Development of vertical compact ion implanter for gemstones applications - S. Intarasiri (2018)
Ion implantation technique was applied as an effective non-toxic treatment of the local Thai natural corundum including sapphires and rubies for the enhancement of essential qualities of the gemstones. Energetic oxygen and nitrogen ions in keV range of various fluences were implanted into the precious stones. It has been thoroughly proved that ion implantation can definitely modify the gems to desirable colors together with changing their color distribution, transparency and luster properties. These modifications lead to the improvement in quality of the natural corundum and thus its market value. Possible mechanisms of these modifications have been proposed. The main causes could be the changes in oxidation states of impurities of transition metals, induction of charge transfer from one metal cation to another and the production of color centers. For these purposes, an ion implanter of the kind that is traditionally used in semiconductor wafer fabrication had already been successfully applied for the ion beam bombardment of natural corundum. However, it is not practical for implanting the irregular shape and size of gem samples, and too costly to be economically accepted by the gem and jewelry industry. Accordingly, a specialized ion implanter has been requested by the gem traders. We have succeeded in developing a prototype high-current vertical compact ion implanter only 1.36 m long, from ion source to irradiation chamber, for these purposes. It has been proved to be very effective for corundum, for example, color improvement of blue sapphire, induction of violet sapphire from low value pink sapphire, and amelioration of lead-glass-filled rubies. Details of the implanter and recent implantation results are presented. © 2014 Elsevier B.V.